Legal support of the rights of the child and the gestational courier in the context of the fourth generation of human rights in Ukraine - STRELNYK, Viktoria; HRES, Natalia; CHURILOVA, Tetiana (Revista Jurídica Portucalense, 2024)
The permissiveness of Ukrainian legislation toward surrogate motherhood makes Ukraine one of the world’s centers for surrogacy. The paper discusses the solution to the issue of ensuring the implementation of human reproductive rights in the international and national legislation of Ukraine. Attention is drawn to the need to consider the norms of morality, ethics, and religion. The purpose of the article is to substantiate the issue of legal support for the implementation of reproductive human rights by considering the theoretical and applied aspects of the violation of the rights of a surrogate mother, a child born to her in the context of the fourth generation of human rights. The authors analyzed international experience in regulating relations in the field of surrogacy (by the example of the USA, Germany, Italy, Spain, and other countries). The authors researched judicial practice, which began to form in Ukraine. Concern was expressed about the lack of effective government response to cases of violation of the rights of a surrogate mother and child on the territory of the state. The authors formulated a proposal on the need for constant state control over organizations that provide mediation and medical services in the field of surrogacy.